Ageing and consumer spending: Some preliminary findings from India and China - Surajit Deb (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2016)
The health care for elderly population remains an important concern in the two populated economies of India and China. This paper provides an attempt to determine the extent of population aging in India and China and subsequently determine the ageing impacts on the aggregate as well as health care expenditures in these two countries, separately for the rural and urban areas. The respective state level (provincial) data from the most recent census information reveal wide regional differences in the levels of population aging in both India and China. The results of our cross-sectional regressions indicate statistically significant and positive impact of population ageing on the total as well as medical expenditures in both the rural and urban regions of India. In the case of China, the impact of old-age population turned out to be insignificant (statistically) on the total consumption expenditures for both the rural and urban areas. As concerns the impacts of ageing on the proportion of health care expenditure, only rural China reveals statistically significant and positive coefficients.
Keywords: J14; D91; I11; C21; O53; 330; Population Ageing; Life Cycle Model; Health Care Expenditures; Cross-Sectional Models; India; China